PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Pengunjung Alibaba Phone Pasuruan) - Wilantika Wilantika; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of Electronic Word of Mouth (E-Wom) on Purchase Intention through Brand Image as a Mediation Variable. The population in this study took from data obtained from the Alibaba Phone Pasuruan Visitors in April - May. Sampling in this study was 89 respondents. The analytical method used with Random Sampling. The results of the study show that e-WOM has a significant effect on Purchase Intention (Case Study on Alibaba Phone Pasuruan visitors). The results of the study have shown that e-WOM has a significantly positive effect on Brand Image on visitors to the Alibaba Phone Pasuruan. Based on the results of the analysis of the influence of e-WOM on Purchase Intention, Sig. equal to 0,00 with beta coefficient value 13,025, Sig value. 0.00 <0.05 indicates that H1 is accepted. This result means that e-WOM has a positive effect on Purchase Intention, the results of the study show that e-WOM has an effect on Purchase Intention. Based on the results of the analysis of the influence of e-WOM on Brand Image, the Sig value is obtained. equal to 0,000 with beta coefficient value 21,073. Sig value. 0,000 <0,05 indicates that H2 is accepted. Based on the analysis of the influence of Brand Image on Purchase Intention, the Sig value is obtained. 0,000 with beta coefficient of 8,695. Sig value. 0,000 <0.05 indicates that H3 is accepted. This result means that Brand Image has a significant positive effect on Purchase Intention. Because the higher the Brand Image that is owned it will affect the Purchase Intention to the visitors of Alibaba Phone Pasuruan. Keyword: Electronic Word Of Mouth (E-Wom), Brand Image, Purchase Intention